LANGUAGE BORROWING: THEORY AND REALITY - Viet, Pham Hung; Thang, Ly Toan (VNU Journal of Foreign Studies, 2017)
The paper discusses the concept of language borrowing from different viewpoints and considers approaches to that linguistic phenomenon, from traditional to modern ones concerning borrowings at different levels in a language system, including phonetic, lexical and syntactic levels. These offer practical implications to research on the issue of borrowing in the Vietnamese language at present.